The “Prosthetic Orthodontic Approach”: An Application of the Biologically Oriented Preparation Technique Protocol - Luca Casula (Case Reports in Dentistry)
In this study, three cases involving patients who required multidisciplinary treatment for the aesthetic and functional rehabilitation of the maxillary or mandibular arch are described. In particular, an indication for preprosthetic orthodontic treatment, such as orthodontic extrusion, tooth realignment, correction of malocclusion, and diastemata closure, was present in all cases. Preprosthetic orthodontic treatment to resolve these issues before the restorative procedures was proposed; however, all patients refused preprosthetic orthodontic treatment. Thus, to restore aesthetics and function, solely a feather-edge prosthetic protocol has been used. The biologically oriented preparation technique was used to prepare the teeth that were moved in the established direction by preparing the abutment more on one side than the opposite. This so called “prosthetic orthodontic approach” allowed resolving clinical issues that would typically require preprosthetic orthodontic treatment, such as complete clinical crown loss, occlusal vertical dimension loss, tooth misalignment, malocclusion, tooth agenesis, and severe multiple diastemata. The degree of reciprocal movement of the prepared teeth achievable through this approach was minor and not comparable to a traditional wide-range orthodontic movement. Besides, the technique resulted in a modification of the gingival tissues and improvement of their thickness although it is unclear what effect this technique has on the gingival biotype. None of the patients had prosthetic or periodontal complications for at least 12 months following the procedure. Gingival health was excellent, and the prosthetic procedure did not affect the pulp survival of the vital teeth. The biologically oriented preparation technique used with a prosthetic orthodontic approach can effectively manage complicated cases without the need for preprosthetic orthodontics.